The phenomenon of the information-meaning field from a cultural-historical perspective - V.T. Kudryavtsev; K.V. Zlokazov; S.N. Enikolopov; N.V. Meshkova; M.S. Rybakova (Культурно-историческая психология)
Based on the concept of personality as a system of relationships (M. Buber, V.N. Myasishchev), the relationship between the visible and meaningful fields (L.S. Vygotsky, A.N. Leontiev), as well as the concept of life space in field theory (K. Lewin), the notion of the information-meaning field is introduced. According to the authors, it allows for a more comprehensive consideration of modern trends in the influence of information on personality and the reciprocal influence of personality on information. An attempt has been made to apply a number of key ideas from the cultural-historical approach of L.S. Vygotsky and his school to analyze the phenomenon of the information-meaning field. This phenomenon is examined within the framework of the social development situation of the modern individual, which is characterized by a problematic nature. A three-dimensional model of the information-meaning field is proposed. The productivity of the topological metaphor for cultural-historical psychology is emphasized, in which it is rooted in its own way (for example, in the concepts of the zone of proximal development and the zone of actual development). The significance of information in the life and development of personality is analyzed, for which it possesses not only instrumental functions. The proposed (psychological) approach to understanding information is based on the correlation of the theoretical concepts of "information" and "meaning" within the boundaries of a person's personal world. At the same time, the experience of other approaches to interpreting the concept of "information" has been analyzed and taken into account. The content of the concept of informational need is revealed in a new way. The mechanism of the formation of the information-meaning field is revealed, and its characteristics are defined from the perspective of the subject who shapes this field. Information becomes a representative of the subject, not only in the sense of a digital trace of its search history but also in a more significant way as a reflection of the prevailing orientation of the personality, its dominant state, and social and asocial needs. The process of constructing the information-meaning field is traced in the form of (1) obtaining information (driven by the satisfaction of informational needs), (2) processing information (mediated by the cognitive capabilities of the individual), and (3) applying information by the person. A brief description of a pilot version of a questionnaire for assessing the psychological parameters of the information-meaning field and the results of its testing are provided.